Fatigue failure load of zirconia-reinforced lithium silicate glass ceramic cemented to a dentin analogue: Effect of etching time and hydrofluoric acid concentration - Monteiro, Jaiane Bandoli [UNESP]; Oliani, Marcelo Gallo [UNESP]; Guilardi, Luis Felipe; Prochnow, Catina; Rocha Pereira, Gabriel Kalil; Bottino, Marco Antonio [UNESP]; de Melo, Renata Marques [UNESP]; Valandro, Luiz Felipe (Elsevier, 2018)
This study aimed to evaluate the effect of etching time and hydrofluoric acid (HF) concentration on the fatigue failure load and surface characteristics of zirconia-reinforced lithium silicate glass (ZLS) ceramic cemented to a dentin-like, fiber reinforced epoxy resin. Ceramic (Suprinity, VITA) (1.0 mm thick) and epoxy resin (2.5 mm thick) discs (10 mm diameter) were produced. The bonding surface of the ceramic samples was nonetched (control group), or etched for 30, 60 or 90 s by 5% or 10% HF. The epoxy resin discs were etched by 10% HF for 30 s followed by the application of an adhesive material (Single Bond Universal, 3M ESPE). Pairs of ceramic/epoxy resin discs were cemented with a dual cure resin cement. The fatigue failure load was determined by the staircase method (500,000 cycles at 20 Hz; initial load = 925 N; step size = 45 N). In 10% HF the etching time was shown to influence the fatigue failure load, which increased as the etching time increased (30 s < 60 s < 90 s), and in 5% HF the fatigue failure load was not shown to be affected by the etching time; the lowest fatigue failure loads were produced in the control group without ceramic etching followed by 10% HF acid etching for 30 s. Topography analysis showed variations based on the etching protocols. All fractures (radial cracks) were shown to originate from defects at the ceramic surface on the cementing interface. For fatigue loading improvements of ZLS ceramic, 10% HF acid etching for 90 s and silanization of the ceramic surface is recommended.
Keywords: Bonding; Cementation; Fatigue; Glass ceramics; Surface conditioning; Topography